Controllable assembly of synthetic constructs with programmable ternary DNA interaction. Issue 12 (17th June 2022) - Cui, Huangchen; Zhang, Tianqing; Kong, Yuhan; Xing, Hang; Wei, Bryan
Abstract: Compared with the dual binding components in a binary interaction, the third component of a ternary interaction often serves as modulator or regulator in biochemical processes. Here, we presented a programmable ternary interaction strategy based on the natural DNA triplex structure. With the DNA triplex-based ternary interaction, we have successfully demonstrated controllable hierarchical assemblies from nanometer scale synthetic DNA nanostructure units to micrometer scale live bacteria. A selective signaling system responsive to orthogonal nucleic acid signals via ternary interaction was also demonstrated. This assembly method could further enrich the diversified design schemes of DNA nanotechnology.